Meat and Nutrition - Lal Ranabhat, Chhabi (IntechOpen, 2021)
This book provides new insights into the production of meat, the burden of diseases associated with excessive meat consumption, undernutrition associated with insufficiency of meat products, and different health-related indicators related to meat and nutrition. This book is useful for researchers, policy makers, and students in medical science, food science, nursing, and public health.